Pride and prejudice of legal imperialism and with reference to preserving English law in Malaysia: making sense of the doctrines of reception and subsequent attraction - Ramalingam, Chithra Latha; Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2019)
A perusal of historical records of Penang, before the island was colonised by the East India Company, shows that the island was inhabited by some Malays and was already the playing ground of the Kedah royalties.6 Therefore, to argue that English law in Penang was ‘settled law’ would be inaccurate and contrary to the above established facts. Interestingly, the evolution of the law is seen during the British empire by taking on colonies and clearly it was to ensure that the heritage of the English law will live on and hence, making English law the law of the colony. The benefit of the British Empire was that by the 18th Century, English’s Law was already well settled in the Malay Peninsular and it was relatively easy to determine which laws that can be received and applied. In light of the above, this article reviews the history of English law in Malay Peninsular with special focus on why the need to review ss 3 and 5 of the Civil Law Act 1956,7 which relates to the current application of English Law in Malaysia